Exposure to Waste Anesthetic Gases Throughout Surgical Interventions: A Case Study in a Portuguese Local Health Unit - Leiddi Leal; Vanessa Yamanaka; Ermelinda Pereira; Joseane Theodoro; Maria de Fátima Domingues; Isabel Fernandes; Marta Fonseca Gabriel; Manuel Feliciano (Atmosphere)
The accumulation of anesthetic gas residues in surgery units can pose health risks to healthcare professionals, highlighting the need to establish effective protection measures. This study evaluated waste anesthetic gas levels in a local health unit in northern Portugal to identify high-exposure areas during surgeries using general anesthesia. Measurements of desflurane, sevoflurane, carbon dioxide, air temperature, and relative humidity were taken during 20 surgeries carried out over approximately six months. The results showed that the thermal conditions were not adequately controlled, particularly the relative humidity levels. The detected WAG concentrations fluctuated across different locations, with concerning peaks being detected in specific settings. Desflurane levels reached 8.79 ppm in the general surgery room (GSR) and averaged 3.13 ppm in the recovery room (RR), while the sevoflurane levels averaged 2.06 ppm in the RR. High concentrations exceeding the recommendations of the U.S. National Institute for Occupational Safety and Health (NIOSH) were notably observed after endotracheal tube removal. In short surgeries, anesthetic gas levels exceeded safety limits, while long surgeries caused peaks in sevoflurane levels. Longer surgeries and higher occupancy were significantly linked to increased levels of WAG and carbon dioxide, emphasizing the need to improve ventilation and environmental controls to safeguard healthcare professionals.